TINJAUAN PELAKSANAAN PROGRAM TANGGAP DARURAT KEBAKARAN DI KANTOR SEKTOR DAN PUSAT LISTRIK PAYA PASIR PT PLN (PERSERO) SEKTOR PEMBANGKITAN MEDAN TAHUN 2013 - Novtalin Hutasoit; Kalsum Kalsum; Umi Salmah (Lingkungan dan Kesehatan Kerja, 2014)
Fires can occur anywhere and anytime without being noticed so can cause much harm either material or fatalities. Fires can occur in a place that has the potential dangers, one of which in Sector Office and Central Electricity Paya Pasir PT PLN (Persero) Sektor Pembangkitan Medan. Losses caused by fire can be minimized by implementing emergency response programs in place that has the fire risk of fire. The purpose of this study is to investigate the implementation of fire emergency response program in Sector Office and Central Electricity Paya Pasir PT PLN (Persero) Sektor Pembangkitan Medan. This study used a inductive approach with interviews of five repondents from emergency response teams in the company to collect information on the implementation of fire emergency response program in the company then will be analyzed with inductive approach. The results showed that the implementation of fire emergency response program include active fire protection equipment, life  saving tool, and fire emergency response management in Sector Office and Central Electricity Paya Pasir PT PLN (Persero) Sektor Pembangkitan Medan is in conformity with the references used in the company in implement the fire emergency response program. The case is expected to be maintained and even enhanced by the company in order to create a safe and comfortable working environment for workers.